Analisis Jumlah Perkara Dispensasi Kawin di PA Sidoarjo sebelum dan sesudah Disahkan UU No. 16 Tahun 2019 - Izzal Majdi (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The main topic of discussion in this research is the age limit for marriage in Islam which is then analyzed by the views of religious leaders regarding the topic of discussion. This study aims to find out how the age limit for marriage in Islam is then analyzed by the Islamic scholars. Islam itself does not limit the ideal age for marriage. But in general what is commonly known is that they are mature, have good sense, are able to distinguish between good and bad so that they can give consent to marry, when the time comes for someone to get married. In the corridor of law regulations, Indonesia provides rules for a minimum age limit for marriage where if the bride and groom have not reached the stipulated age, then they must go through the process of requesting dispensation from marriage at the local religious court. The problem is, the various reasons put forward by the applicant for the marriage to be carried out immediately. In this study, the author will describe the dynamics of the issue of marriage dispensation at the Sidoarjon religious court in the range before and after 2019. Keywords: dispensation of marriage, early age, child marriage.